Pengembangan Modul Pembelajaran Berbasis Pancasila yang Terintegrasi HOTS pada Mata Kuliah Aljabar Linear Elementer - Friska Ledina Situngkir; Imelda; Sinta Dameria Simanjuntak; Meikardo Samuel Prayuda; Liana; Jakobus Ginting (Pustaka Karya Mandiri, 2026)
This study aims to develop a Pancasila-based learning module integrated with Higher Order Thinking Skills (HOTS) for the Elementary Linear Algebra course that meets the criteria of validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The analysis stage included needs analysis, curriculum analysis, student characteristics, learning materials, and the integration of Pancasila Student Profile values and HOTS indicators. The module was designed by organizing learning structures, HOTS-oriented activities, and Pancasila values, then validated by four experts in subject matter, instructional design, educational evaluation, and character education. The revised product was implemented with 20 students of the Mathematics Education Study Program enrolled in Elementary Linear Algebra. Data were collected through observation, interviews, questionnaires, HOTS tests, and documentation, and were analyzed descriptively using validity, practicality, effectiveness, and normalized gain analyses. The results show that the module obtained an average validity score of 3.82, categorized as highly valid. Student responses reached 93%, indicating that the module was highly practical. The module also improved students' average HOTS score from 60.40 in the pretest to 86.70 in the posttest, with an N-Gain score of 0.66. Classical learning mastery reached 90%, while the implementation of Pancasila values obtained an average score of 92.17%. These findings indicate that the module is feasible as an innovative teaching material supporting Outcome-Based Education and character strengthening in higher education.